Gestión administrativa y desempeño laboral de los colaboradores de Comercializadora San Juan, 2023 - Gamarra Alvarez, Barbara Samanta (2024)
The title of this study is “Employee administration and job performance in commercial companies in San Juan de Iquitos in the year 2023.” Your general question is: ¿What is the relationship between management and employee performance at Comercializadora San Juan, 2023? General objective: Determine the relationship between the administrative work performance and the work performance of the employees of Comercializadora San Juan in the year 2023. Hypothesis: There is a relationship between the administrative work performance of the employees of Comercializadora San Juan in the year 2023 and the performance administrative labor of the employees of Comercializadora San Juan. in 2023. Again using quantitative methods, applying appropriate criteria and a non-experimental design, the population will consist of 47 employees and the sample will be selected through random, convenience or non-probabilistic sampling. The tool to measure variables is a questionnaire and statistics are used to test measurements and test hypotheses using the chi-square statistic. Research Conclusion: There is a direct correlation between administration and employee performance at Comercializadora San Juan, Province of Iquitos, 2023. Therefore, a positive correlation is observed with “Pearson Chi Square” = 0.000. This allows us to believe that the performance of Comercializadora San Juan employees will be greater as long as it is well managed.